Factor Associated with Health Professions’ Burnout: A Systematic Review - Widiatmoko, Dita Pambudi; Achadi, Anhari (Universitas Serambi Mekkah, 2020)
AbstractOne of the factors that lead to a decrease of ineffectiveness in the workplace is burnout. Burnout is asyndrome of depersonalization, emotional exhaustion, and a sense of low personal accomplishment. Theburnout phenomenon is found in almost all health professions. Health professions’ burnout is an aspectthat can affect the quality of healthcare services. This was a systematic review following the PRISMAmodel. The review was conducted by reading published articles written in English from 2014 to 2019from the electronic databases. A total of 6 full articles were included in this study. Some variablesshowed a positive correlation with health professions’ burnout, including age, gender, marital status, length of work, and income/payment. Burnout has a negative effect on health professions’ job satisfaction and affects the quality of healthcare services.Keywords: Burnout, determinant, health professions, healthcare